Assessing Oral Communication Skills of Students in Business Administration Department - ASTUTY, Ani Dyah (Politeknik Negeri Ujung Pandang, 2023)
This research article presents an assessment of the oral communication skills of students in the Business Administration Department. A questionnaire was used to measure 95 students' self-perceived ability in oral communication for various activities. The study aimed to identify areas of strengths and weaknesses in students' oral communication skills and highlight potential areas for improvement. The findings revealed that students rated themselves low in the category of